Sclerostin, an emerging therapeutic target for treating osteoporosis and osteoporotic fracture: A general review - Pui Kit Suen (Journal of Orthopaedic Translation, 2016)
Osteoporosis and its associated fracture risk has become one of the major health burdens in our aging population. Currently, bisphosphonate, one of the most popular antiresorptive drugs, is used widely to treat osteoporosis but so far still no consensus has been reached for its application in treatment of osteoporotic fractures. However, in old patients, boosting new bone formation and its remodelling is essential for bone healing in age-related osteoporosis and osteoporotic fractures. Sclerostin, an inhibitor of the Wnt/β-catenin signalling pathway that regulates bone growth, has become an attractive therapeutic target for treating osteoporosis. In this review, we summarize the recent findings of sclerostin and its potential as an effective drug target for treating both osteoporosis and osteoporotic fractures.